Thermal plasticity of coral reef symbionts is linked to major alterations in their lipidome composition - Marina T. Botana; Adriano B. Chaves‐Filho; Alex Inague; Arthur Z. Güth; Flavia Saldanha‐Corrêa; Marius N. Müller; Paulo Y. G. Sumida; Sayuri Miyamoto; Matthias Y. Kellermann; Raymond C. Valentine; Marcos Y. Yoshinaga (Limnology and Oceanography, 2022)
Coral bleaching caused by ocean warming is leading to worldwide coral decline. The physiological processes underlying this ecological event are still incompletely understood, although previous research has suggested oxidative stress as major player in the impairment of symbiont thylakoid membranes and in symbiosis breakdown. Lipids are interesting targets of investigation, given their susceptibility to thermal and oxidative stresses. Here, an untargeted lipidomic approach was employed to examine changes in lipidome and pigments of three coral reef symbionts (Symbiodiniaceae) after a heat shock in in vitro experiments. The acute thermal stress induced species‐specific changes in lipidome and pigments compositions of both heat sensitive and tolerant symbionts. Heat sensitivity was characterized by a steep and steady decline in cell densities over time (4 and 240 h after heat shock). At the membrane level, heat sensitive symbiont displayed a quantitative decrease in glycolipids linked to polyunsaturated fatty acids, followed by enrichment in oxidized lipids and sphingolipids. Despite showing distinct adaptations, the two heat tolerant symbionts were characterized by the preservation of membrane lipids after heat shock, particularly glycolipids. This finding suggests the action of powerful antioxidant systems, preventing the escalation of oxidized lipids concentration in thylakoid membranes under thermal stress. Although limited by the examination of free‐living symbionts, our study provides a solid baseline for the investigation of lipidome and pigments alterations of Symbiodiniaceae in response to heat stress. Novel potential lipid biomarkers linked to thermal stress are suggested. In particular, oxidized lipids—which are implicated in coral symbiosis establishment and breakdown—appear as attractive targets for further research.